Step-by-step explanation:
5(2h+8) <60
10h +40< 60
10h + 40-40 < 60-40
10h < 20
10h/10 < 20/10
h < 2
Answer:
Your supposed to cancel out 12 on both sides so u subtract 12 on both sides so the equation would be
-3x= -52
Step-by-step explanation:
Answer:f(x)= -8 (4x) will be the reflected function across x-axis for the function g(x).
Explanation: since we know that the image or reflection of x along x-axis = -x
That is, when we talk about a function's reflection across any axis then we have to replace variable according to that axis. For example if you have a line x=3 in positive x-axis then you can also draw a similar line x=-3 in negative x-axis. so, you can say, x=-3 is the reflection of x=3 along x axis.
Similarly, for an another line y=3, y=-3 is a reflection.
thus in the case of g(x) we can find the reflection across x-axis after replacing x by -x.
we have g(x) =8(4x)
replace x by -x we get g(-x)= 8(4×-x)= 8(-4x)=-8(4x)
so -8(4x) is the reflection of g(x)
but according to the question f(x) is the reflection of g(x) across x-axis.
Thus, f(x)=-8(4x)
Answer:
-x + 4
Step-by-step explanation:
(4x+5)+(−5x−1)
4x+5−5x−1 [Remove the parentheses]
-x + 4 [Combine Like Terms]
Answer:
a). -65
b). -61
c). -20ab + 3bc +3ac
Step-by-step explanation:
According To the Question,
a). the sum of 72 − 104 + 5 and -32 + 4 - 10 .
- (72 − 104 + 5) + (-32 + 4 - 10)
- (-27) + (-38)
- -27 - 38
- -65
b). What should be added to 32 + 32 + 3 to get 3 + 3 , Let X be Added .
- Thus, (32 + 32 + 3) + X = 3 + 3
- 67 + X = 6
- X = 6 - 67
- X = -61
c). Subtract the sum of 12ab –10bc –18ac and 9ab + 12bc + 14ac from the sum of ab + 2bc and 3bc – ac.
- Thus, [(ab + 2bc) + (3bc – ac)] - [( 12ab –10bc –18ac) + (9ab + 12bc + 14ac)]
- (ab + 5bc - ac) - (21ab + 2bc - 4ac)
- ab + 5bc - ac - 21ab - 2bc + 4ac
- -20ab + 3bc + 3ac